Aptamers against Cells Overexpressing Glypican 3 from Expanded Genetic Systems Combined with Cell Engineering and Laboratory Evolution. Issue 40 (7th September 2016) - Zhang, Liqin; Yang, Zunyi; Le Trinh, Thu; Teng, I‐Ting; Wang, Sai; Bradley, Kevin M.; Hoshika, Shuichi; Wu, Qunfeng; Cansiz, Sena; Rowold, Diane J.; McLendon, Christopher; Kim, Myong‐Sang; et al.
Abstract: Laboratory in vitro evolution (LIVE) might deliver DNA aptamers that bind proteins expressed on the surface of cells. In this work, we used cell engineering to place glypican 3 (GPC3), a possible marker for liver cancer theranostics, on the surface of a liver cell line. Libraries were then built from a six‐letter genetic alphabet containing the standard nucleobases and two added nucleobases (2‐amino‐8 H ‐imidazo[1, 2‐ a ][1, 3, 5]triazin‐4‐one and 6‐amino‐5‐nitropyridin‐2‐one), Watson–Crick complements from an artificially expanded genetic information system (AEGIS). With counterselection against non‐engineered cells, eight AEGIS‐containing aptamers were recovered. Five bound selectively to GPC3‐overexpressing cells. This selection–counterselection scheme had acceptable statistics, notwithstanding the possibility that cells engineered to overexpress GPC3 might also express different off‐target proteins. This is the first example of such a combination. Abstract : Six nucleobases : An expanded genetic information system and laboratory in vitro evolution were used to generate six‐nucleotide aptamers that target cells engineered to overexpress a particular cell‐surface protein. These aptamers could be used to distinguish cells that display that protein from those that do not.